2020
DOI: 10.1088/1757-899x/987/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gas Flow Rate on Plasma Parameters Produced by a Plasma Jet and its Spectroscopic Diagnosis Using the OES Technique

Abstract: In this study, the emission spectra of plasma generated from the argon gas in a plasma jet system were measured under normal atmospheric pressure, at constant voltage and for different flow rates from 1–5L/min. The plasma parameters were calculated based on electron density, frequency of plasma, the temperature of an electron, Debye length and the number of particles in the Debye sphere. We employed optical emission spectrometer (OES) technology, which captured the spectrum resulting from the plasma at various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The plasma glow volume was observed to increase with flow velocities in the experiments (less than 10 mm along the plasma tube). Although the plasma parameters listed in table 1 were not sensitive to flow velocities in the Langmuir probe measurement, several studies on atmospheric pressure plasma jet have observed that flow velocity can affect plasma geometry and plasma parameters in the plasma bulk [42][43][44]. As illustrated by figures 7 and S4, when plasma parameters are changed, simulated particle charge distributions differ given a constant residence time.…”
Section: Numerical Modeling Resultsmentioning
confidence: 98%
“…The plasma glow volume was observed to increase with flow velocities in the experiments (less than 10 mm along the plasma tube). Although the plasma parameters listed in table 1 were not sensitive to flow velocities in the Langmuir probe measurement, several studies on atmospheric pressure plasma jet have observed that flow velocity can affect plasma geometry and plasma parameters in the plasma bulk [42][43][44]. As illustrated by figures 7 and S4, when plasma parameters are changed, simulated particle charge distributions differ given a constant residence time.…”
Section: Numerical Modeling Resultsmentioning
confidence: 98%
“…The bandgap energy of films near the absorption edge was determined using the Tauce method through the following formula 17 where α is the linear absorption coefficient, B is a constant, hν is the photon energy, and Eg is the bandgap energy for NPs with direct and indirect bandgap energy. It is possible to calculate Eg of the film by plotting (αhν)2 versus hν and extrapolating the straight line to the photon energy axis.…”
Section: Ultra Violet Spectroscopic Analysis Of Znsementioning
confidence: 99%
“…The primary mechanism for PLAL nanomaterial fabrication can be illustrated as follows: laser-matter interaction (absorption of a laser pulse by a material); the formation, expansion, and cooling of a plasma plume; the generation of shock waves; and the formation, expansion, and collapse of bubbles in a liquid medium 14 17 . While in the plasma jet technique a wide range of reactive oxygen and nitrogen species (RONS) produced by atmospheric pressure non-thermal plasma sources is crucial to this application 22 , 29 . Since plasma-generated RONS alter the chemical makeup of a liquid, plasma-liquid interactions are crucial in the production of nanomaterials 29 33 .…”
Section: Introductionmentioning
confidence: 99%
“…While in the plasma jet technique a wide range of reactive oxygen and nitrogen species (RONS) produced by atmospheric pressure non-thermal plasma sources is crucial to this application 22 , 29 . Since plasma-generated RONS alter the chemical makeup of a liquid, plasma-liquid interactions are crucial in the production of nanomaterials 29 33 . Ozone, singlet oxygen, hydrogen peroxide, hydroxyl radicals, and nitric oxide are just a few of the common RONS that are created during plasma-liquid interactions 8 , 34 .…”
Section: Introductionmentioning
confidence: 99%